2018
DOI: 10.1002/ardp.201800086
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and glutathione reductase inhibitory properties of 5‐methyl‐2,4‐dihydro‐3H‐1,2,4‐triazol‐3‐one's aryl Schiff base derivatives

Abstract: Glutathione reductase (GR) is responsible for the existence of the reduced glutathione (GSH) molecule, a crucial antioxidant against oxidative stress reagents. The antimalarial activities of some redox active compounds are attributed to their inhibition of antioxidant flavoenzyme GR, and inhibitors are therefore expected to be useful for the treatment of malaria. In this work, a fast and effective synthesis and the GR inhibitory properties of 5-methyl-2,4-dihydro-3H-1,2,4-triazol-3-one's aryl Schiff base deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Researchers studied that the impacts of Schiff base derivatives on baker's yeast GR. These compounds were displayed as effective inhibition profiles (Balaydın et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers studied that the impacts of Schiff base derivatives on baker's yeast GR. These compounds were displayed as effective inhibition profiles (Balaydın et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Eurasian Chemical Communications applied in nonlinear optical materials [7], corrosion inhibitors [8], and synthesis of nano-compounds [9][10][11][12]. Some of them have also inhibitory activities against αglucosidase [13], carbonic anhydrase [14,15], urease [16], cholinesterase [17], glutathione reductase [18]. Schiff bases also serve as versatile ligands for coordinating a variety of transition metal ions in different coordination geometries and oxidation states [19,20].…”
Section: Original Research Articlementioning
confidence: 99%
“…GR enzyme activity was performed according to the Beutler method [11]. In order to determine the activity of GR enzyme from baker's yeast, the decrease of NADPH in the presence of the substrate GSSG (oxidized glutathione) was done by spectrophotometrically at 340 nm under the assay condition at 25°C, 100 mM Tris-HCl buffer pH 8.0 [5].…”
Section: Measurement Of Glutathione Reductase Activitymentioning
confidence: 99%
“…Inhibition of the GR enzyme has been studied using many different compounds. As a result of these trials, it was observed that there was a decrease in GSH / GSSG ratio and an increase in NAD(P)H / NAD(P) + ratio [4][5][6]. In some studies, it has been determined that the inhibition of the GR enzyme does not affect the production of free radicals or the expression of other enzymes involved in GSH biosynthesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%